Effects of different uphill interval-training programs on running economy and performance - Barnes, K. R.; Hopkins, W. G.; McGuigan, M. R.; Kilding, A. E. (International Journal of Sports Physiology and Performance, 2013)
Purpose: Runners use uphill running as a movement-specific form of resistance training to enhance performance. However, the optimal parameters for prescribing intervals are unknown. The authors adopted a dose-response design to investigate the effects of various uphill interval-training programs on physiological and performance measures. Methods: Twenty well-trained runners performed an incremental treadmill test to determine aerobic and biomechanical measures, a series of jumps on a force plate to determine neuromuscular measures, and a 5-km time trial. Runners were then randomly assigned to 1 of 5 uphill interval-training programs. After 6 wk all tests were repeated. To identify the optimal training program for each measure, each runner`s percentage change was modeled as a quadratic function of the rank order of the intensity of training. Uncertainty in the optimal training and in the corresponding effect on the given measure was estimated as 90% confidence limits using bootstrapping. Results: There was no clear optimum for time-trial performance, and the mean improvement over all intensities was 2.0% (confidence limits ±0.6%). The highest intensity was clearly optimal for running economy (improvement of 2.4% ± 1.4%) and for all neuromuscular measures, whereas other aerobic measures were optimal near the middle intensity. There were no consistent optima for biomechanical measures. Conclusions: These findings support anecdotal reports for incorporating uphill interval training in the training programs of distance runners to improve physiological parameters relevant to running performance. Until more data are obtained, runners can assume that any form of high-intensity uphill interval training will benefit 5-km time-trial performance.